Hubungan Peran Bidan, Posisi Menyusui, Kondisi Puting Dengan Kejadian Bendungan ASI Ibu Post Partum - Ageng Septa Rini; Dionysia Artinigsih; Agus Santi Br Ginting (STIKes Santa Elisabeth Medan, 2023)
Post Partum ASI Dam swelling of the breasts due to increased venous and lymph flow, causing breast milk dams and pain accompanied by an increase in body temperature. Purpose To find out the relationship between the midwife's role, breastfeeding position, nipple condition and the incidence of ASI dams in post partum mothers at PMB A Jakarta in 2022. Method in this study used quantitative research with analytic descriptive research and used a cross sectional design, samples in 30 postpartum mothers, using Chi-Square. Results, with a P-Value of 0.011 and an OR value of 1.048, there is a relationship between Breastfeeding Position and the incidence of ASI dams in postpartum mothers at PMB A Jakarta in 2022, with a P-Value of 0.014 and an OR of 2.091 and there is a relationship between Nipple Condition and the incidence of ASI dams in postpartum women at PMB A Jakarta in 2022, with a P-Value of 0.009 and an OR of 1.643. In conclusion, it is hoped that midwives can teach mothers directly when breastfeeding how to do the correct breastfeeding position.